The Role of ECG-Gated CT in Patients with Bicuspid Aortic Valve Replacement: New Perspectives in Short- and Long-Term Followup. (23rd October 2012) - Sperandio, Massimiliano; Arganini, Chiara; Bindi, Alessio; Fusco, Armando; Olevano, Carlo; Bertoldo, Fabio; Romagnoli, Andrea; Chiariello, Luigi; Simonetti, Giovanni
Abstract : The aim of our study was to compare the results of the TTE (transthoracic echocardiography) with the results obtained by the ECG-gated 64 slices CT during the followup of patients with bicuspid aortic valve (BAV), after aortic valve replacement; in particular we evaluated the aortic root and the ascending aorta looking for a new algorithm in the followup of these patients. From January 1999 to December 2009 our attention was focused on 67 patients with isolated surgical substitution of aortic valve; after dismissal they were strictly observed. During the period between May and September 2010, these patients underwent their last evaluation, and clinical exams, ECG, TTE, and an ECG-gated-MDCT were performed. At followup TTE results showed an aortic root of36.7 ± 4 mm and an ascending aorta of39.6 ± 4.8 mm. ECG- gated CT showed an aortic root of37.9 ± 5.5 mm and an ascending aorta of43.1 ± 5.2 . The comparison between preoperative and postoperative TTE shows a significant long-term dilatation of the ascending aorta while the aortic root diameter seems to be stable. ECG-gated CT confirms the stability of the aortic root diameter (38.2 ± 5.3 mm versus37.9 ± 5.5 mm; <0.0001) and the increasing diameter value of the ascending aorta (40.2 ± 3.9 mm versus43.1 ± 5.2 mm;P = 0.0156 ). Due to the different findings between CT and TTE studies, ECG-gated CT should no longer be considered as a complementary exam in the followup of patients with BAV, but as a fundamental role since it is a real necessity.